STUDY OF FLAVOUR MODIFICATION ON PROCESSING OF SHREDDED TUNA FISH (Euthynussp) - Kevin Eka Putra; Sukirno Mus; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was aimed to determine of flavour modification on processing of shredded tuna fish towards consumer acceptance. The fresh tuna fish as raw material was obtained from coastal areas West Sumatera (Bungus). The method used in this research was experimental method with Completly Randomized Design non factorial with 3 levels of treatment, i.e.natural flavour (AT0), rendang flavour (AT1), and curry flavour (AT2) with 3 replicates.The result showed that the best treatment of shredded tuna fish was rendang flavor (AT1) with 28 panelists (35%) with characteristics: yellowish brown appearance, slightly dry texture, typical rending flavour, typical rendang aroma and strong turmeric smell, followed by AT2 (curry flavour) with 27 panelists (34%) with caharecteristics: light brown appearance, dry texture, typical curry flavour, typical curry aroma and AT0 treatment (natural flavour) with 25 panelists (31%) with caharacteristis brown appearance, less dry texture, tasty less goodand fishy taste still strong, aroma was rather fishy. Keywords: shredded fish, Euthynussp, consumer acceptance.